2020
DOI: 10.4136/ambi-agua.2611
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Activity of the Seed Extract from Zygia cauliflora (WILLD.) KILLIP applied in Water Treatment

Abstract: The use of natural coagulants is a promising alternative to replace or assist chemical coagulants due to its numerous advantages. This paper evaluates the effectiveness of a natural coagulant in water treatment. The coagulant was extracted from the Zygia cauliflora (Willd.) Killip seed in saline solutions and defatted using 95% ethanol. The tests were conducted using different concentrations of the coagulant (0.1, 0.5, 1.0, 2.0, 3.0, and 4.0 g L-1) and of NaCl (0.0 M, 1.0 M, and 5.0 M). The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The data applied to the Temkin isotherm model indicate that the adsorption of MB dye onto Zeo-FPT (1F:1Z) was inferior, with the R 2 of 0.732 and the adsorption heat of 9.36 kJ mol −1 . Domingues et al (2020) [ 27 ] studied the use of Zygia cauliflora seeds for water purification, and found that the adsorption mechanism was best described by the Freundlich isotherm model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data applied to the Temkin isotherm model indicate that the adsorption of MB dye onto Zeo-FPT (1F:1Z) was inferior, with the R 2 of 0.732 and the adsorption heat of 9.36 kJ mol −1 . Domingues et al (2020) [ 27 ] studied the use of Zygia cauliflora seeds for water purification, and found that the adsorption mechanism was best described by the Freundlich isotherm model.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their highly lignocellulosic composition and low ash content, date palm tree components have been intensively assessed recently with respect to their suitability for assembling enacted carbon at minimal expense [ 25 ]. In contrast to commercial activated carbon, the activated carbon obtained from date palm trees has prominent textural qualities that provide it with a notably greater adsorption limit for water remediation purposes [ 27 ]. The important biomass components of fiber of palm tree (FPT) include hemicellulose (18%), cellulose (46%), ash (10.54%), and lignin (20%) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%